Human Resources of Research and Innovation in Indonesia: Reality, Policy Strategy, and Roadmap - Prakoso Bhairawa Putera; Ida Widianingsih; Yan Rianto; Sinta Ningrum; Suryanto Suryanto (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
This article reveals the reality, policy strategies, and roadmap plans for human resource development in Indonesia's research and innovation field. The result of human resources in a lot of research and innovation is an important one, especially after the government's commitment through the issuance of Presidential Regulation Number 18 of 2020 concerning the National Medium-Term Development Plan (RPJMN) for 2020-2024 and also the Presidential Decree of the Republic of Indonesia Number 21 of the Year 2021 concerning the National Talent Management Task Force, where research and innovation are one of the sectors developed in national talent management. This study uses a qualitative method with a descriptive approach. The investigation resulted in four aspects of concern, namely the existing conditions and the Indonesian government's experience in developing human resources in the field of research and innovation, which had been initiated since the era of President Soekarno, then the presence of a scholarship program created by Prof. Eng. BJ Habibie, who at that time served as Minister of State for Research and Technology by providing scholarships to more than 1,500 people during 1982-1996 to study in several countries which would later become talents for the national strategic industry and research and development institutions in Indonesia. The results of talent management policy mapping in the research and innovation sector are discussed in the next section. To enrich understanding, a comparative study of talent management and policy was carried out in Japan, the Philippines, and Malaysia. In the end, a proposed strategy and roadmap for implementing research talent and innovation in Indonesia are presented.